Assessing New Product Sustainability Index (NPSI) by Integrating Sustainability Aspects into the Early New Product Design Stages - Abdulamir Bektas Wali; Mahmoud Abbas Mahmoud; Jamal Nasir H. Al Khatib (Engineering and Technology Journal, 2012)
Product design is one of the most important stages in the new product development process influencing global sustainability. However, the early design strategy offers the highest impact on sustainability, the need for using sustainable proactive approach in early design decisions could be the effective tool to achieve sustainability of new products. This paper presents a necessity of considering the sustainability aspects in pre-specification stages of new product design process, and introduces a modified methodology for establishing a single Index termed as New Product Sustainability Index (NPSI) which enables the designers to carry out a quick analysis of the alternatives of new product designs and make choices based on various criteria. The index aggregates (TBL) and R & D aspects of different types of quantitative and qualitative indicators and information objects from a product manufacturing point of view, into one single index. The sustainability matrix, aspects and criteria used in evaluating of (NPSI), is constructed in table form.